Cinética de fotodegradação do polímero MEH-PPV por espectroscopia uv-visível em tempo real – aplicação em dosimetria 3D - Raicoski, Michelle Leifeld (2020)
In this present work, we investigated the photodegradation kinetics of the poly-(5-methoxy-2-(2-ethyloxy)-p-phenylene-vinylene) polymer (MEH-PPV) and the development of a 3D dosimeter. For the kinetic study, photodegradation of the MEH-PPV solution in chloroform was induced using a diode laser at 405 nm (ultraviolet region of the electromagnetic spectrum). Three main changes were observed in the absorption spectrum as a function of the excitation time: I) the absorption band of the lowest-energy transition (transition π → π *) decreases in amplitude as a function of time; II) the absorption band shifted to shorter wavelengths (higher energy) and III) there is an increase in the linewidth of the absorption band. All of these effects suggest that there is a split in the polymer chain. Also, the experiments were carried out in different concentrations (2.94 x 10-4 mol/L, 1.98 x 10-4 mol/L, 1.20 x 10-4 mol/L and 3.75 x 10-5 mol /L) and laser powers (30 mW and 105 mW). From these data, it was observed that the MEH-PPV photodegradation to follow a pseudo-first-order reaction with a photodegradation rate value of 6.7 x10-5 s-1 for 30 mW and 2.26 x 10-4 s-1 for 105 mW. When we normalize the rate value by the power, we observed the same value of approximately 2.20 x 10-3 J-1. Therefore, our results show that neither the concentration nor the excitation power modifies the photodegradation kinetics of MEH-PPV in chloroform. To better understand this process, photoluminescence measurements of the MEH-PPV in solution were performed. Our results have shown that UV radiation causes a structural disorder in the polymer, reaching a maximum in 30 minutes for the laser power of 105 mW. This phenomenon may be associated with an epoxidation process that leads to polymeric chain scission and consequently decreases the effective conjugation length of MEH-PPV. For the development of the 3D dosimeter prototype, polymethylmethacrylate (PMMA), polyvinylpyrrolidone (PVP), and MEH-PPV solutions were used. The 3D dosimeter was exposed to the same excitation laser, and a high-resolution color CCD camera put to 90 degrees in relation to the laser beam captured the fluorescence images at intervals of 30 seconds for 3 hours. Through this set of images, a color map was built, which indicates the regions where the dosimeter received most of the radiation. The computational method used is called generalized differences. Through this methodology, it was possible to obtain a visual result of the photodegradation distribution along the dosimeter. The method showed that it has the potential to map the dosage received over the volume (3D dosimetry). Furthermore, from a temporal analysis, that is, from color maps generated now in shorter time intervals (30 minutes), it was possible to quantify the degradation of the material from the DG signal, and we observed that in solid-state the MEH-PPV follow first-order kinetics.